PENERAPAN SMART E-COMMERCE GUNA PENGEMBANGAN PRODUK LOKAL DESA TAHUNAN KECAMATAN TEGALOMBO PACITAN - Fauzan Fasykur; Mohammad Bhanu Setyawan (Universitas Muhammadiyah Ponorogo, 2019)
As the Country with the 8th largest internet user in the World, it makes its own opportunity for entrepreneurs in Indonesia to market their products through the internet. The opportunity is still very open because macroeconomic growth will increase with the presence of digital business. One form of media to market local products is to use e-commerce, which grows too, which means that opportunities are still very broad. E-commerce with all its growth can touch various sectors starting from agriculture, industry, public sector, populist economy and so on can be used to develop all potential in the region. As in the Tegalombo Annual Village, Pacitan Regency, which has a mountainous / hilly geographical area, has all the abundant agricultural potential and human resources that are quite capable but have not been exposed to the maximum. For example the results of empon-empon processing and the results of youth creativity that impressed the road in place due to constrained marketing problems and the development of various local products. With the existence of e-commerce it is very possible to overcome the obstacles in marketing these local products. Supported by internet connectivity that is already connected in the village, ecommerce only requires creative hand touches to realize e-commerce as a solution for developing all village potential.